Design and characterization of telecentric f-θ scanning lenses for broadband terahertz frequency systems - Zachery B. Harris; Stefan Katletz; Mahmoud E. Khani; Arjun Virk; M. Hassan Arbab (AIP Advances, 2020)
Telecentric beam scanning using f-θ lenses offers nearly uniform spot size, linear beam displacement, and normal incidence angle over a planar surface. These unique properties allow for the minimization of imaging distortion over a wide field-of-view. In this article, we present a numerical method for designing custom f-θ lenses in the THz regime. We fabricated three lenses made from different commonly used polymer materials in the THz optics. We demonstrated their optical performance metrics compared to a conventional plano-convex lens over the broadband 0.3 THz–1 THz range. We find that the f-θ lens designed using the optical properties of high-density polyethylene achieved superior performance by maintaining a constant phase over a wide field of view of about 34°. We demonstrate this isophase property by measuring a constant time of arrival of the THz time-domain pulses over a reference mirror with a standard deviation of ∼19 fs, in excellent agreement with simulation predictions. This work will pave the way for the design and implementation of highly precise and fast telecentric imaging systems in the THz frequencies.